Environmentally relevant concentrations of F–53B induce eye development disorders-mediated locomotor behavior in zebrafish larvae. (December 2022) - Wu, Luyin; Zeeshan, Mohammed; Dang, Yao; Liang, Li-Ya; Gong, Yan-Chen; Li, Qing-Qing; Tan, Ya-Wen; Fan, Yuan-Yuan; Lin, Li-Zi; Zhou, Yang; Liu, Ru-Qing; Hu, Li-Wen; et al.
Abstract: The perfluorooctane sulfonate alternative, F–53B, induces multiple physiological defects but whether it can disrupt eye development is unknown. We exposed zebrafish to F–53B at four different concentrations (0, 0.15, 1.5, and 15 μg/L) for 120 h post-fertilization (hpf). Locomotor behavior, neurotransmitters content, histopathological alterations, morphological changes, cell apoptosis, and retinoic acid signaling were studied. Histology and morphological analyses showed that F–53B induced pathological changes in lens and retina of larvae and eye size were significantly reduced as compared to control. Acridine orange (AO) staining revealed a dose-dependent increase in early apoptosis, accompanied by upregulation of p53, casp-9 and casp-3 genes. Genes related to retinoic acid signaling ( aldh1a2 ), lens developmental ( cryaa, crybb, crygn, and mipa ) and retinal development ( pax6, rx1, gant1, rho, opn1sw and opn1lw ) were significantly downregulated. In addition, behavioral responses (swimming speed) were significantly increased, while no significant changes in the neurotransmitters (dopamine and acetylcholine) level were observed. Therefore, in this study we observed that exposure to F–53B inflicted histological and morphological changes in zebrafish larvae eye, induced visual motor dysfunctions, perturbed retinoid signaling and retinal development and ultimately triggering apoptosis. Graphical abstract: Image 1 Highlights: F–53B induce small eye and histopathological abnormalities in larvae eye. F–53B induce dose-dependent manner apoptosis in larvae eye. mRNA levels involved in eye developmental were significantly changed. F–53B induces locomotor behavior perturbed eye development disorders.